Effects of Dietary Supplementation with Epigallocatechin Gallate on Meat Quality and Muscle Antioxidant Capacity of Broilers Subjected to Acute Heat Stress - Fei Zhao (MDPI AG, 2021)
This study evaluated epigallocatechin gallate’s (EGCG’s, 400 mg/kg) effect on meat quality and muscle antioxidant status of broilers under acute heat stress (AHS). A total of 144 21-day-old male Huainan partridge chickens were randomly allocated to the EGCG-free group (12 replicates) and the EGCG group (6 replicates). On day 94, the EGCG-free group was divided into the control group (CON) and the AHS group, and then AHS group and EGCG group (identified as AHS + EGCG group) were treated with AHS (33 ± 1 °C for 12 h). AHS increased (p < 0.05) L*24h, drip loss, muscle lactic acid, malondialdehyde (MDA) contents, and kelch-like ECH-associated protein 1 (Keap1) mRNA level, and decreased (p < 0.05) eviscerated percentage, pH24h, a*, muscle total superoxide dismutase (T-SOD) activity, the ratio of T-SOD/MDA and glutathione peroxidase /MDA, glycogen content, and nuclear factor erythroid 2-related 2 (Nrf2), catalase (CAT), NAD(P)H/quinone dehydrogenase 1 (NQO1) mRNA levels. The AHS + EGCG group exhibited lower (p < 0.05) L*24h, drip loss, muscle lactic acid, MDA contents and Keap1 mRNA level, and greater (p < 0.05) eviscerated percentage, pH24h, a*, muscle T-SOD activity, the ratio of T-SOD/MDA, Nrf2, and NQO1 mRNA levels compared with the AHS group. In conclusion, EGCG protects against AHS-impaired meat quality by improving muscle antioxidant capacity, which seems to be associated with the activation of the Nrf2 signaling pathway.